Physicochemical and leaching properties of coal ashes from Malaysian coal power plant - Abd Manan T.S.B.; Beddu S.; Mohamad D.; Mohd Kamal N.L.; Wan Mohtar W.H.M.; Khan T.; Jusoh H.; Sarwono A.; Ali M.M.; Che Muda Z.; Mohamed Nazri F.; Isa M.H.; et al. (Elsevier B.V., 2023)
Coal; Coal ash; Construction industry; Copper metallography; Fossil fuel power plants; Heavy metals; Leaching; Lead metallography; Scanning electron microscopy; Zinc metallography; Ash samples; Atomic absorption spectrometers; Coal power plants; Malaysians; Standard guidelines; Toxicity characteristics; X ray fluorescence; Physicochemical properties